Isotherm Adsorption of Cd(II) Using Surfactant-Modified Activated Carbon-Sodium Lauryl Sulfate (SMAC-SLS) - Side, Sumiati (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Heavy metal pollution such as Cd(II) in the environment is a serious issue that requires effective solutions. This study aims to evaluate the ability of sodium lauryl sulfate surfactant modified activated carbon (SMAC-SLS) in adsorbing Cd(II) from solution. SMAC-SLS synthesis was carried out using wet impregnation method with SLS solution. The adsorption process was tested at various concentrations of Cd(II), and the results were analyzed using Langmuir and Freundlich isotherm models. The results showed that the adsorption of Cd(II) on SMAC-SLS followed the Freundlich isotherm model, with R2 of 0.995, Kf of 1.934 mg/g, and nnn of 5.039, indicating excellent adsorption on the heterogeneous surface. The Langmuir model also gave an R2 of 0.9767 with a maximum adsorption capacity Qmax of 11.83 mg/g and adsorption energy of 22.517 kJ/mol, indicating a possible chemisorption mechanism. Modification of activated carbon with SLS was shown to increase the adsorption capacity as well as the interaction with Cd(II) ions. This suggests that SMAC-SLS has great potential as an adsorbent in the treatment of wastewater containing heavy metals.